Coordinated host-pathogen transcriptional dynamics revealed using sorted subpopulations and single macrophages infected with Candida albicans - José F. Muñoz (Nature Portfolio, 2019)
The outcomes of the interactions between individual host cells and pathogens are heterogeneous. Here, the authors assess transcriptional variability in both host and pathogen during infection of macrophages with the fungus Candida albicans, using sorted subpopulations and single macrophages.